ChemInform Abstract: Monofluorination of Organic Compounds: 10 Years of Innovation. Issue 45 (November 2015) - Champagne, Pier Alexandre; Desroches, Justine; Hamel, Jean‐Denys; Vandamme, Mathilde; Paquin, Jean‐Francois
Abstract Review: 685 refs.